Ion Chromatographic Determination of Nitrite and Nitrate in Tobacco Leaf - Wu, Li; Song, Ze-Min; Chen, Yong-An; Zhu, Hong-Ying; Li, Zhang-Hai; Gao, Yun; Yang, Jun; Hung, Yi-De (Asian Journal of Chemistry, 2013)
A method for simultaneous determining NO2– and NO3– in tobacco leaf with ion chromatography was established by using internal standard quantitation based on Br–. Tobacco samples were pretreated by ultrasonic extraction and solid phase extract clean up and then the resulting supernatants were injected into a high capacity anion exchange column with suppressed conductivity detection. The detection limits of NO2– and NO3– were 4.7 and 2.4 μg/L, respectively. Recovery were both above 95 % and RSD for either ion was less than 5 %. The method is simple, rapid, accurate, reliable and suited for the analysis of NO2– and NO3– in tobacco leaf samples.